A Hospital-based Survey on the Prevalence of Bronchial Asthma in Patients with Allergic Rhinitis in Southern China. Issue 6 (November 2013) - Hong, Haiyu; Yang, Qintai; Zuo, Kejun; Chen, Xinye; Xia, Wentong; Lv, Minhui; Li, Xiaomin; Xu, Geng; Li, Huabin; Fan, Yunping
Background: The prevalence of bronchial asthma (BA) and the underlying risk factors in patients with allergic rhinitis (AR) in China are largely unknown. Thus, this study is designed to assess the BA comorbidity in AR patients in two cities (Guangzhou and Zhuhai) of southern China and to determine the risk factors of BA in these AR patients. Methods: We performed a cross-sectional, hospital-based survey in two modernized cities in southern China. The BA prevalence was evaluated in 1931 AR patients. Participants were asked to complete a questionnaire containing specific items for AR and BA. A logistic regression analysis was used to assess the risk factors of BA comorbidity in AR patients. Results: The prevalence of concomitant BA in AR patients is 5.33% (103/1931). Most of the participants (98.4%) were sensitized to more than one allergen, and the most common sensitization was to house-dust mites. The strongest risk factor of BA determined by a multiple logistic regression analysis was a duration of AR of >5 years (adjusted odds ratio [OR], 8.67; 95% confidence interval [CI], 3.74–20.06), followed by smoking (adjusted OR, 7.21; 95% CI, 1.86–8.23) and self-medication with antibiotics (adjusted OR, 6.35; 95% CI, 3.43–11.78). Conclusion: Our findings suggested the risk factors of concomitant BA in AR patients may be helpful to establish preventive strategies.